Trait Predictors of Online Impulsive Buying Tendency: A Hierarchical Approach - Sun, Tao; Wu, Guohua (Journal of marketing theory and practice, 2011)
The Internet represents a new marketing channel that can stimulate buying impulsiveness. With Mowen's 3M model as a theoretical framework, this paper examines the trait predictors of this online buying tendency. Buying impulsiveness (surface trait) is positively affected by Internet addiction (situational trait), need for arousal (elemental trait), and need for material resources (elemental trait). It is negatively affected by task orientation (compound trait). Emotional instability (elemental trait) has a positive effect on Internet addiction. Conscientiousness (elemental trait) has a positive effect on task orientation. Theoretical and practical implications are provided.